PERANCANGAN SISTEM PERAWATAN PREVENTIF TIME BASED MAINTENANCE DI LABORATORIUM PEMESINAN DASAR POLMANBABEL - Hafizh Al Karim; Dwipa Prasetiansyah; Indra Feriadi; Fajar Aswin (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The machine tools in Polman Babel's basic machining laboratory are deteriorating and are damaged due to misoperation, maintenance, and age. This study aims to identify failure problems and design a time based preventive maintenance system in the laboratory. The research was carried out with the stages of identifying problems and system requirements, system design, and system design testing. This study sets the first priority of problem solving is to design a periodic maintenance system that can be implemented in accordance with the laboratory management system. The system designed consists of maintenance plan data, annual maintenance schedule, monthly maintenance program, inspection check sheet, maintenance data sheet, machine history card, and maintenance implementation procedures. The results of the system verification and validation test indicate that the system design can be understood by laboratory managers and can be applied in educational laboratories.